The roles of valerenic acid on BDNF expression in the SH-SY5Y cell - Ekrem-Murat Gonulalan; Omer Bayazeid; Funda-Nuray Yalcin; Lutfiye-Omur Demirezer (Elsevier, 2018)
The roots of Valeriana officinalis L. (Valerianaceae) are used for treating sleep disorders and/or mild nerve tension. The effect of valerenic acid on brain-derived neurotrophic factor (BDNF) has not yet been studied, although it is known that gamma-amino butyric acid A (GABAA) receptor is regulated by BDNF, which modulates the depressive-like behavior and neurogenesis. The purpose of this study is to determine the effect of V. officinalis root extract (VO), its main constituents valerenic acid (VA) and acetoxy valerenic acid (AVA) as well as valerenic acid-free (VAF), acetoxy valerenic acid-free (AVAF) extracts and increasing amounts of valerenic acid containing extracts on the BDNF expression in SH-SY5Y cell lines. The effect of methanolic extracts of VO, VA, AVA, VAF, AVAF, and the extracts whose amount of VA were increased gradually, were tested using a Human BDNF ELISA kit with 17β-estradiol as a positive control. The VO and VA extracts caused a significant (p < 0.001) increase in the BDNF expression in SH-SY5Y cells compared to control. This effect completely disappeared when cells were treated with VAF extract. AVA alone did not show any significant change in the BDNF levels. The extracts with increasing amount of VA led to a concentration- dependent effect on the cells. In conclusion, our findings suggest that the antidepressant-like effect of the VO extract is also related to BDNF expression, and that this is mainly due to the presence of VA in the extract. Removing VA from VO extract leads to a loss of activity. Moreover, the concentration of VA plays a role for BDNF expressions in SH-SY5Y cells, which demonstrates the importance of quality control on the commercially available products. Keywords: Valerenic acid, Valerian, Valeriana officinalis L., BDNF, SH-SY5Y